2007
DOI: 10.1186/1471-2148-7-195
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of feeding specialization in Tanganyikan scale-eating cichlids: a molecular phylogenetic approach

Abstract: Background: Cichlid fishes in Lake Tanganyika exhibit remarkable diversity in their feeding habits. Among them, seven species in the genus Perissodus are known for their unique feeding habit of scale eating with specialized feeding morphology and behaviour. Although the origin of the scale-eating habit has long been questioned, its evolutionary process is still unknown. In the present study, we conducted interspecific phylogenetic analyses for all nine known species in the tribe Perissodini (seven Perissodus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 42 publications
1
56
0
Order By: Relevance
“…Indeed, our studies based on mantel test confirmed the role of genetic factors in influencing morphology. In addition, links between morphological and genetical differentiation have been reported by Stewart and Albertson (2010), who integrated both genetic and geometric morphometric approaches in studying scale eating cichlids of Lake Tanganyika, which had been reported to show frequency balanced polymorphism in the left-handedness and right-handedness of the mouth, an adaptation previously reported by Takahashi et al (2007). Their morphometric results strongly supported the genetic basis of jaw laterality.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, our studies based on mantel test confirmed the role of genetic factors in influencing morphology. In addition, links between morphological and genetical differentiation have been reported by Stewart and Albertson (2010), who integrated both genetic and geometric morphometric approaches in studying scale eating cichlids of Lake Tanganyika, which had been reported to show frequency balanced polymorphism in the left-handedness and right-handedness of the mouth, an adaptation previously reported by Takahashi et al (2007). Their morphometric results strongly supported the genetic basis of jaw laterality.…”
Section: Discussionsupporting
confidence: 67%
“…More significantly, studies have shown that phylogenetic information can indeed be gleaned from AFLP data (26), and a growing body of literature (e.g., refs. [27][28][29] attests to the ability of AFLP-derived phylogenies to corroborate other sources of data. Finally, it is encouraging that (i) the AFLP phylogenies of H. erato and H. melpomene show such strong geographic coherence, which would not be expected if the data were dominated by homoplasy; and (ii) our results from Structure analyses are largely consistent with those from the phylogenetic analyses of our AFLP data.…”
Section: Discussionmentioning
confidence: 74%
“…We suggest that the lepidophagic activity of this species is related to its rheophilic features, i.e., it involves specialized senses and behavior that have developed in the fast current waters of the embanked Tocantins River. Contrary to the scale-eating specialization among Perissodini cichlids, hypothesized to have arisen in deep water habitats in the African Great Lakes (Takahashi et al, 2007;Koblmüller et al, 2007), the origin of lepidophagy among the characids might have occurred in lotic waters. More comprehensive comparative studies within a phylogenetic framework upon the diet of scale eater characids could probably shed light on the evolution of this specialized feeding habit in the Neotropical region.…”
Section: Discussionmentioning
confidence: 83%